A comparission study of locally probiotic with imported probiotic in microbial balance of broiler gastro-intestinal tract - Al-Kaissy, Galib A. (The Iraqi Journal of Veterinary Medicine, 2005)
This study aimed the effect of adding 0.5 and 1 kg of imported probiotic/ton feed (T1 and T2) compared with the a percentages of 1.5, 3 kg locallyprobiotic / ton (T3 and T4) when as T5 used feed free of probiotic .500 dayoldchicks were distributed into five treatments and subdivided into two replicates(50 chicks per replicate) to study the effect of adding the two probiotics in themicrobial balance of broiler gasto-intestinal tract .The results obtained revealedthe following:-Adding percentages of locally or imported probiotic (T1, T2, T3 andT4)decreased significantly (P<0.01) log no.of Coliform count and fungi count atmid point of intestine (Jejunum), crop and cecum of broiler, at the same timeAdding the two probiotics increased significantly (P<0.01) log no.ofLactobacilli count compared with control group (T5) .Whenas significantdifferences in the log no. of total bacterial count at mid point of intestine andcrop. Also no significant differences between locally or imported probiotic werenoticed in the studied microbial counts or to the adding percentages. Conclosionis the importance of adding probiotics to the feed for optimum microbial balanceto increase resistance of broiler to pathogenic bacteria.